2016
DOI: 10.3390/geriatrics1030017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Review of Fitness-to-Drive and Return-to-Driving Following Traumatic Brain Injury

Abstract: The purpose of this study was to conduct an evidence-based review to determine predictors of fitness to drive and return to driving in persons with traumatic brain injury (TBI). Relevant databases (MEDLINE/PubMed, CINAHL, Cochrane Library, and SCOPUS) were searched for primary articles published before June 2016 using MeSH search terms. Using the American Academy of Neurology’s classification criteria, 24 articles were included after reviewing 1998 articles. Studies were rated by class (I–IV), with I being the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In Austria, assessment involves testing driving abilities and the driver's willingness to adapt to traffic conditions, while in Portugal perceptive-cognitive, psychomotor, and psychosocial dimensions are included in their psychological exam for safe driving behavior. Switzerland, Sweden, and Italy have their legal frameworks for assessing fitness to drive (Schuhfried, 2015;Palubiski & Crizzle, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Austria, assessment involves testing driving abilities and the driver's willingness to adapt to traffic conditions, while in Portugal perceptive-cognitive, psychomotor, and psychosocial dimensions are included in their psychological exam for safe driving behavior. Switzerland, Sweden, and Italy have their legal frameworks for assessing fitness to drive (Schuhfried, 2015;Palubiski & Crizzle, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Cyr and colleagues (2009) observed that in a simulated driving environment, TBI survivors who resumed driving were significantly more likely to crash in reaction to a surprising and challenging event compared with noninjured matched control individuals. A recently published literature review found no standard neuropsychological tests for predicting driving performance of TBI survivors (Palubiski & Crizzle, 2016). Nevertheless, a better characterization of the cognitive limitations of TBI survivors in the specific context of driving could be translated into an adapted retraining effort that could combine a cognitive training protocol within a driving context (Ross, Ponsford, Di Stefano, Charlton, & Spitz, 2016).…”
mentioning
confidence: 99%